Legal Pluralism and Indigenous Justice Systems: An Anthropological Analysis - Tanjung, Muhammad Arifin (Jurnal Ar Ro'is Mandalika (Armada), 2023)
Legal pluralism refers to the coexistence of multiple legal systems within a single society, often including both state-based and indigenous or customary justice systems. This article provides an anthropological analysis of legal pluralism and indigenous justice systems, exploring the complexities and implications of their interaction. Drawing on qualitative methods, literature studies, and library research, the paper examines how legal pluralism shapes social norms, power dynamics, and access to justice in diverse cultural contexts. It critically evaluates the challenges and opportunities presented by the recognition and integration of indigenous justice systems into broader legal frameworks, highlighting issues of cultural relativism, human rights, and legal reform. Through an interdisciplinary approach, the article offers insights into the complex dynamics of legal pluralism and indigenous justice, shedding light on the ways in which these systems intersect and influence each other. By examining case studies from various regions and communities, the research underscores the importance of understanding the cultural, historical, and socio- political factors that shape legal pluralism and indigenous justice systems. Ultimately, this analysis contributes to broader discussions on legal diversity, social justice, and the role of anthropology in understanding legal phenomena.